Lactobacillus rhamnosus: An emerging probiotic with therapeutic potential for depression - Jing Feng; Qiuyu Cen; Yanru Cui; Xiaomin Hu; Min Li; Linjie Wang; Juanfang Wei; Nianyi Sun; Junyu Wang; Anren Zhang (Pharmacological Research)
Depression, a complex psychological disorder, involves multiple biological pathways in its pathogenesis. In recent years, the gut-brain axis theory has provided novel insights into the pathogenesis of depression, particularly the crucial role of the gut microbiota in mood regulation. While there remains no universal consensus on the most efficacious strains for depression treatment, Lactobacillus rhamnosus has risen to prominence within the realm of probiotics for its potential to positively modulate depressive symptoms. This review preliminarily explores the clinical significance of Lactobacillus rhamnosus in the treatment of depression and summarizes the potential mechanisms by which Lactobacillus rhamnosus treats depression, including its regulation of gut microbiota, alterations in gene expression, improvement of intestinal barrier function, maintenance of neurotransmitter balance, suppression of inflammatory responses, modulation of the immune system, coping with oxidative stress, and optimization of metabolic processes. Future research needs to further explore these mechanisms and combine them with clinical research results to optimize treatment plans and provide more effective treatment options for patients with depression.